Assessment of voltage and current quality indices of grid connected solar PV plants against international standards - Ramachandaramurthy V.K.; Yong J.Y.; Tan K.M.; Pouryekta A.; Jayasinghe D.H.G.A.E.; Ekanayake J.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric distortion; Information systems; Information use; Natural resources; Renewable energy resources; System stability; Distributed generators; International standards; Performance assessment; Real time measurements; Renewable energy source; Research communication; Solar photovoltaics; Technological advances; Solar power generation